2019
DOI: 10.3390/ma12244034
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Different Types of Basic Oxygen Furnace Slag Filler and its Influence on Properties of Asphalt Mastic

Abstract: The fillers of ordinary and pyrolytic basic oxygen furnace (BOF) slag were selected to investigate the properties of their asphalt mastic. XRF (X-Ray Fluorescence) was used to analyze chemical composition of fillers. Meanwhile, SEM (Scanning Electron Microscope) and AIMS (Aggregate Image Measurement System) were utilized to explore meso-morphology, angularity and sphericity. Penetration, softening point and viscosity of asphalt mastic were discussed, while the rheological properties of asphalt mastic were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The effective utilization of industrial wastes to improve the engineering properties of asphalt concretes has been demonstrated by several researchers, in terms of the partial or total replacement of the coarser part of the limestone aggregate structure [5][6][7][8][9][10][11][12][13]. The largest part of the world's road network (almost 95%) is built with flexible pavements [14]; therefore, the use of waste materials in flexible pavement construction can be more advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…The effective utilization of industrial wastes to improve the engineering properties of asphalt concretes has been demonstrated by several researchers, in terms of the partial or total replacement of the coarser part of the limestone aggregate structure [5][6][7][8][9][10][11][12][13]. The largest part of the world's road network (almost 95%) is built with flexible pavements [14]; therefore, the use of waste materials in flexible pavement construction can be more advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al [ 21 ] came to a similar conclusion and proposed that the steel slag fillers content should be lower than 75% by volume. Kong et al [ 22 ] selected different basic oxygen furnace slag filler to investigate its influence on properties of asphalt mastic and the results showed the fillers could increase high temperature anti-rutting stability of asphalt concrete but reduce low-temperature flow performance of asphalt mastic. Notwithstanding, the performance of asphalt mastics with SSF stand a good chance of differing from that with limestone fillers (LF) under different aging methods, due to the fact that the pore-structure of steel slag has the potential to reflect less energy and refract more energy more easily [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt binder, aggregate, and mineral filler are the three major elements of asphalt concrete. Aggregate, which accounts for more than 90% of the total volume of asphalt concrete, as the primary skeleton plays a key role in resisting vehicle load [5,6]. e quality of aggregate has remarkable impacts on road performance and life period [7,8].…”
Section: Introductionmentioning
confidence: 99%